Balancing Tradition and Protection: Child Marriage in the Practice of Islamic Family Law - Maswan, Maswan; Toni, Muhammad; Wahyudi, Untung; Sari, Nurma; Netti, Misra (Yayasan Marwah Madani Riau, 2025)
Child marriage remains a pressing issue in Indonesia despite legal reforms aimed at increasing the minimum age for marriage. This study conducted in Siak, Riau Province, Indonesia for explores how the practice of Islamic family law influences the persistence of child marriage, focusing on the tension between traditional religious interpretations and contemporary child protection efforts. The aim is to understand how religious court decisions, sociocultural norms, and interpretations of Islamic legal principles contribute to the continuation or mitigation of child marriage in Muslim communities. Using a qualitative approach, data were collected through in-depth interviews with religious court judges (hakim agama), community leaders, and affected families in selected West Java and Central Java regions. Document analysis of court decisions regarding marriage dispensation was also conducted to examine the reasoning behind legal allowances for underage marriages. The findings reveal that while many religious judges express concern for child protection, they often face social and religious pressures to approve marriage dispensations, especially in cases involving premarital pregnancy or economic vulnerability. Cultural traditions and local interpretations of Islamic law frequently prioritize family honor and social conformity over legal age requirements. However, some progressive interpretations are emerging, emphasizing maqāṣid al-sharī‘ah (the higher objectives of Islamic law), especially the protection of minors. This study concludes that balancing tradition and protection requires a contextual rethinking of Islamic legal practices in Indonesia. Greater emphasis on the ethical goals of Islamic law, combined with community education and judicial training, can help reduce the incidence of child marriage. The research highlights the need for an integrated approach that respects religious values while safeguarding children's rights.